Peran Self-Control Dalam Memediasi Pengaruh Komitmen Organisasi, Lingkungan Kerja Dan Stres Kerja Terhadap Perilaku Cyberloafing : Survei Pada Pegawai Pengadilan Agama Korwil 1 Pengadilan Tinggi Agama Bandung - Yamin Mubarok; Ade Komaludin; Edy Suroso (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The aim of this research was to determine and analyze the role of self-control in mediating the influence of organizational commitment, work environment, and work stress on cyberloafing behavior among employees of the Religious Court Regional Coordinator I of the High Religious Court of Bandung. The method used in this study was a survey with a descriptive quantitative approach. The sample size in this study was 230 respondents, determined using the saturated sample technique. Using Partial Least Square-Structural Equation Model (PLS-SEM), the study found that organizational commitment and work environment had a significant positive effect on self-control, while work stress had a significant negative effect on self-control. Organizational commitment had a significant negative effect and work stress had a significant positive effect on cyberloafing behavior, while work environment had no effect on cyberloafing behavior. Self-control had a significant negative effect on cyberloafing behavior. Self-control was able to mediate the influence of organizational commitment, work environment, and work stress on cyberloafing behavior among employees of the Religious Court Regional Coordinator I of the High Religious Court of Bandung.